The relation of the specific acoustic impedance of liquids and the surface tension - NIEMCZEWSKI, Bogdan (Archives of Acoustics, 1976)
Theorems for the dependence of the specific acoustic impedance (ςc) of organic liquids on the surface tension (σ) are proposed and substantiated. It was found that for a given liquid the quotient N = ςc/σ is constant at different temperatures. For liquids with similar chemical structure N = ςc/σ &= const. Formulae for the sound propagation velocity and its temperature coefficient which permit the evaluation of the said parameters from the density and surface tension of a liquid are given. An analysis of the accuracy of the values of sound velocities has been made and the temperature coefficients Δc/Δt calculated for ten liquids, have been compared with the coefficients obtained by experiment. A reversal of the relationship for N permits calculation of the surface tension with an accuracy that is sufficient for practical purposes.